Web-based contractor evaluation system for mass-housing projects in Turkey - Arslan, Gokhan (Journal of Civil Engineering and Management, 2012)
Determining the most appropriate contractor for a construction project is a highly critical issue. Selecting the right contractor for the right job can significantly influence the overall project performance. In the selection process, construction clients have to know all financial, technical and general information about the contractors to determine the most appropriate one for the project. Within this context, clients should consider several criteria that may include quality of production, adequacy of technical staff and financial stability. In this study, a survey was carried out among 52 construction professionals working at the Public Housing Development Administration (PHDA) in Turkey. The objective of this survey is to examine the relative weights of the criteria that have been using by this owner in the construction contractor selection process. Afterwards, a web-based contractor evaluation system, WEB-CONTEST, by which the contractors can be evaluated based on a combined criterion, is proposed. The system facilitates the contractor selection process and enables the construction owner to select the most correct contractors for its relevant projects.